Long-term effects of biomechanical exposure on severe knee pain in the Gazel cohort - Descatha, Alexis; Cyr, Diane; Imbernon, Ellen; Chastang, Jean-François; Plenet, Aurélia; Bonenfant, Sébastien; Zins, Marie; Goldberg, Marcel; Roquelaure, Yves; Leclerc, Annette (Scandinavian Journal of Work, Environment & Health, 2011)
' ' OBJECTIVE ': 'Little is known about the long-term effect of occupational determinants on knee pain. We aimed to assess whether the risk factors for severe knee pain, observed with a cross-sectional approach, were still relevant after retirement, 12 years later. ' ' METHODS ': 'All men participating in the ARPEGE side study of the GAZEL cohort (employees of the French national utility for energy production and distribution, recruited in 1989) and who answered the 1994 or 1995 general GAZEL self-administered questionnaire, were included. Weight and self-reported exposures over the entire working life were collected at baseline. Knee pain and its intensity were recorded in 1994–1995 and again in 2006. Moderate and severe knee pain, defined from an intensity or discomfort scale (threshold 3 on a 6-level scale in 1994–1995, and 4 on an 8-level scale in 2006), were the main outcomes. ' ' RESULTS ': 'At baseline, 1786 men were included. In 1994–1995, moderate knee pain was observed among 10.3% and severe pain in 12.8% of men. In 2006, 1482 men (83%) answered the questionnaire. Moderate and severe knee pain were observed in 18.6% and 16.3% of respondents, respectively. Working in a kneeling or squatting position was significantly associated with severe knee pain at baseline, taking into account age, sports, smoking habits, and body mass index [adjusted odds ratio (ORadj) 1.4, 95% confidence interval (95% CI) 1.1–1.9 for “ever exposed” and ORadj 2.0, 95% CI 1.3–3.1 for >25 years of exposure]. In 2006, when most subjects were retired, the association between working in a kneeling or squatting position and severe pain was weaker but still significant (ORadj 1.4, 95% CI 1.04–1.85). ' ' CONCLUSIONS ': 'The effect of high knee exposure in the working life on severe knee pain remains even after retirement, although decreased. An extended surveillance and prevention program for these workers could be proposed.
Keywords: biomechanical exposure; cohort; exposure; GAZEL cohort; knee; knee pain; long-term effect; occupational factor